EXAMINATION OF PUBLIC MOTHER'S KNOWLEDGE ABOUT BENGKUNG CULTURE ON ASI PRODUCTION IN THE WORKING AREA OF BONTONYELENG PUBLIC HEALTH CENTER - Sumarni; Sri Ningsih; Kurniati Akhfar; Nur Afni; Hasriyuni (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2019)
Bengkung culture is a long strand of cloth that is wrapped around the waist many times until the end of the cloth runs out which is commonly used by post-natal mothers in Java and Bugis areas. The culture of using bengkung by some postpartum mothers in the Bontonyeleng Community Health Center is believed to be postnatal care and is believed to increase breast milk. The purpose of this study was to examine the knowledge of postpartum mothers about the culture of bengkung on breast milk production at the Bontonyeleng Health Center which has a level of knowledge based on the understanding of the benefits and procedures for using bengkung. This type of research is descriptive with a survey research design. The sampling technique was accidental sampling with a total of 30 respondents, the research instrument used a test sheet. The results of the study on 30 respondents in the working area of ??the Bontonyeleng Health Center had a level of knowledge in the category of less (100%). This is influenced by the level of education, age and occupation. In general, they believe that the use of jicama is used to produce breast milk, the information is obtained from close family even though they do not know the size of the type of cloth used. Medically, the use of jicama is not affected by the increase in breast milk production. Conclusion: the knowledge of postpartum mothers in the working area of ??the Bontonyeleng Health Center Kec.Gantarang Kab.Bulukumba majority is at the level of less knowledge, as many as 30 people (100%)